Audio-Visual Based Arabic Learning Through Social Media: Youtube, Tiktok, Instagram, Facebook - Syarofi, Ach; Syuhadak, Syuhadak (Kitaba, 2023)
Arabic language learning in the digital era that demands global communication skills that students must have, teachers need to use social media in audio-visual based learning such as Youtube, Tiktok, Instagram and Facebook. The use of social media has an influence in audio-visual based Arabic language learning, namely: increasing learning motivation, improving listening skills, increasing vocabulary mastery, improving speaking skills, easily accessible, and increasing creativity. Although social media has influence and advantages, it also has disadvantages that must be anticipated. The most prominent drawback of social media is the presence of negative audio-visual content that is not worth showing to students. Therefore, teachers must be qualified facilitators in filtering content so that teaching materials on social media are in accordance with learning objectives.